How Healthcare Utilization Due to Dizziness and Vertigo Differs Between Older and Younger Adults - Prell, Tino; Finn, Sigrid; Axer, Hubertus (Frontiers in Medicine, 2022)
Background: Vertigo and dizziness are common in older adults. We describe self-reported healthcare utilization because of dizziness and vertigo in older adults attending a tertiary care specialized vertigo center. Methods: Data from 765 patients (45% were ≥60 years old) with chronic dizziness and vertigo who attended a daycare multimodal treatment program were recorded. Data included sociodemographic parameters, dizziness-related characteristics, the Body Sensations Questionnaire (BSQ), the Agoraphobic Cognitions Questionnaire (ACQ), and the Hospital Anxiety and Depression Scale (HADS). Also, healthcare utilization, including 1) physician and clinical services, 2) hospitalizations in the year before consulting the vertigo center, 3) prescription of drugs and other professional services were included. Descriptive statistics, exploratory data analysis, and regression models were used. Results: Intensity of dizziness was similar in both age groups, however, distress due to dizziness was more severe in younger persons. Dizziness symptoms lasted longer in older adults than in younger persons. Older adults had a somatic diagnosis (74.6 vs. 35.0%) more frequently and reported more falls (37.2 vs. 28.5%) than younger individuals. Anxiety about bodily sensations was higher in younger patients (mean BSQ1 = 9.33 ± 5.6) than in older patients (mean BSQ1 = 6.72 ± 5.4). Older persons had fewer depressive symptoms (mean HADS depression = 5.8 ± 3.6 vs. 6.5 ± 4.1) and less anxiety (mean HADS anxiety = 5.7 ± 3.7 vs. 7.8 ± 4.1) than younger individuals. Younger people were more frequently hospitalized (24.4%) than older adults (16.3%) in the year before consulting the vertigo center. Also, younger patients and patients with non-somatic etiologies had considerably more consultations with healthcare providers than older patients. Older adults received less medication (50.3%), less physiotherapy (41%), and less psychological therapy (11.6%) for vertigo than younger people (59.7%, 52.2%, 20.4% respectively). Conclusion: Age-associated differences in healthcare utilization were defined in selected patients attending a specialized vertigo center. Since dizziness is frequently a heterogeneous disorder requiring interdisciplinary care, its diagnostic and therapeutic work-up must be improved for older patients with dizziness.